2023
DOI: 10.1038/s41598-023-34425-z
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative investigation of spark plasma on skin parameters with skin elasticity, thickness, density, and biometric characteristics

Abstract: Cold atmospheric plasma has been developed and utilized as a novel technique for skin rejuvenation because of its various effects on cells and living things. This study investigated the accuracy of this claim and any possible side effects of using spark plasma to rejuvenate skin. The present work is the first quantitative investigation using animal models. 12 Wistar rats were divided into two groups for this investigation. To compare the skin's natural process with the treated skin, the first group underwent a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The plasma exeresis medical devices ionize the atmospheric gas between the device and the skin, sublimate the surface layers, and uniformly heat it. [9][10][11] Plasma exeresis is an innovative, minimally invasive technique that has been gaining attention in dermatology. Plasma has been widely used in treating moles, telangiectasia, stretch marks, acne scars, skin rejuvenation, and skin tightening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The plasma exeresis medical devices ionize the atmospheric gas between the device and the skin, sublimate the surface layers, and uniformly heat it. [9][10][11] Plasma exeresis is an innovative, minimally invasive technique that has been gaining attention in dermatology. Plasma has been widely used in treating moles, telangiectasia, stretch marks, acne scars, skin rejuvenation, and skin tightening.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Ghasemi et al, investigating the effect of plasma exeresis on skin parameters on rat models, it was concluded that plasma exeresis improves skin thickness, density, and elasticity, most likely due to increased keratinocytes and fibroblasts. 9 In one study conducted by Rossi et al, the efficacy of using plasma was evaluated in 250 patients with benign skin lesions (dermal nevi, fibroma, keratosis, xanthelasma), nonsurgical blepharoplasty, wrinkles (perioral, glabellar, neck, and preauricular regions), active acne, and scarring (postacneic and posttraumatic). The results revealed that plasma exeresis is extremely reliable and safe, without having any permanent side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies show that NO signi cantly impacts the skin, speci cally on the proliferation of keratinocytes and broblasts [16], [22], [26] Epidermis thickening brought on by cold plasma is most likely caused by the proliferation of keratinocytes [16], [22], [26]. However, CAP can initially weaken the skin barrier and dry up the top layer of the epidermis.…”
Section: Discussionmentioning
confidence: 99%